0227 PROSPECTIVE MEMORY PERFORMANCE NEGATIVELY CORRELATES WITH SLOW-WAVE SLEEP. (28th April 2017) - Cunningham, TJ; Pardilla-Delgado, E; Payne, JD
Abstract: Introduction: Prospective memory (PM), or the ability to plan and spontaneously remember to execute activities in the future, is a vital, everyday life skill. Recent evidence demonstrates that sleep enhances PM, particularly in the context of a semantic categorization task (Scullin and McDaniel, 2010). The goal of the present study was to determine the generalizability of sleep's benefit on PM and its relationship to sleep stages. Methods: Participants were divided into wake (n=30) and sleep (n=30) groups. Wake participants arrived at 9am and completed a battery of cognitive tests including three ongoing tasks: living/nonliving decision, lexical decision, and semantic categorization. After the final task, a PM instruction for the next session was given (i.e., hit "q" whenever "table" or "horse" appears), followed by a distractor task. Wake participants were dismissed for 12hr of wakefulness before a second session that included another round of the ongoing tasks and a PM test for the critical words. Sleep participants completed the same experimental design, but arrived at 9pm and had a 12-hour delay that included a night of polysomnograph-recorded sleep. Results: Results showed no main effect of task type, indicating that performance was similar across all tasks. Importantly, the sleep group performed significantly better on overall PM performance than the wake group [t(58)=2.0, p=0.05]. Within the sleep group there was a negative correlation between PM performance and percentage of SWS [r(30)=-0.39, p=0.03], such that individuals with higher percentages of SWS during the night had worse PM performance. Conclusion: These results suggest that sleep protects the ability to successfully perform future actions across multiple contexts and is not limited to testing modality. Further, we found a negative association between PM performance and SWS, which is interesting in light of recent evidence suggesting that SWS impairs gist memory (Pardilla-Delgado et al., 2016). We suggest that given the generalizable (i.e. not based on individual experiences) nature of a PM instruction, prospective memory and gist memory may have overlapping sleep consolidation networks, such that while a night of sleep benefits PM, the detail-focused episodic memory benefit of SWS reduces time spent consolidating prospection-based memory. Support (If Any):